The musical dimension of perception in the upper Congo, Zae - Carrington, John F. (International Library of African Music, 1971)
Writing in 1591, Pigafetta relates the experience of a Portuguese explorer, Duarte Lopez, in what is now Angola. After describing a kind of guitar which he found there, he goes on to say: More than this (and very wonderful), by means of this instrument they indicate all that other people would express by words of what is passing in their minds and by merely touching the strings signify their thoughts. (Pigafetta p. 111). Soon after I arrived myself in Central Africa, I was confronted with an experience similar to that of Duarte Lopez. An Olombo man who possessed a guitar sese (a so-called Hova guitar, brought into this area by the Arab slave-traders at the turn of the century) invited me to hide a coin in the clothing of one of his friends who formed a ring around him and said he would guarantee that another friend who had not seen where the coin was placed would be able to find it without any difficulty. I accepted the challenge and listened carefully to the guitar. The man found the coin easily and repeated the performance without me being able to see or hear any messages from the guitarist. I had to admit that I was baffled by what I had seen and that there was some feature of their perception which remained hidden from me. Some years later, when I had begun to study the way in which musical tone-patterns are important for speech in this part of Africa, I realised how these Olombo villagers had mystified me
Keywords: Ethnomusicology; Music; Tone color (Music); Africa; Central Africa; Zaire; African Music